Salon de Mars 1990. (Paris : Medi - Art, 1990)
Drouillet, Gérard ; De la Villéglé, Jacques ; Poliakoff, Serge ; Witkin, Joël-Peter ; Riopelle, Jean-Paul ; Herbin, Auguste ; Fontana, Lucio ; etc.
Salon de Mars 1990, Champ de Mars, Paris, 21 - 26 mars 1990
boek